Stock de carbono en el suelo de bosque varillal seco y húmedo en la zona de Nina Rumi, Loreto- Perú, 2021 - Angulo Pinedo, Mauri Guillermo (2022)
In the present study, the capacity of the carbon stock stored in the soils of the dry vine forest and moist vine forest in the Nina rumi River Nanay area was determined. To obtain the soil samples, the area has been georeferenced in five (05) points, for each point five (05) pits of 70 cm x 70 cm x 30 cm deep have been made, obtaining a total of 30 samples of dry soils and humid in metal cylinders whose volume was 180 cm3 to obtain apparent density, percentage of organic matter and percentage of carbon and carbon stock in t/ha. The results obtained were that the largest stock of carbon in the soil of the dry vagal forest and humid vagal forest is concentrated at 00 cm - 10 cm depth with an average of 82.69 t/ha, and 47.97 t/ha. respectively. The statistical analysis of the population normality test using Kolmogorov-Smirnov shows that it is not parametric (p>0.05), for both types of soil; the statistical test of analysis of variance of Kruskal-Wallis for dry soils of varal forest is significant (p)= 0.0185; and Dunn's statistical test shows significance between 00-10 cm and 20-30 cm. While for wet soils it is not significant (p)= 0.0758. Comparing the analysis of variance of the carbon stock between dry and wet varal soils, it is significant at (p) Kruskal.Wallis=0.0051.